A MODEL OF PROACTIVE BEHAVIOR IMPROVEMENT BASED ON PROCESS CONTROL, WORKLOADS AND INTRINSIC MOTIVATION IN A SOCIAL CAPITAL CONTEXT (Study in the Criminal Investigation Unit of Rembang Police Resort) - Annisa Faridhotun Ni’mah; Tatiek Nurhayati (UNISSULA, 2017)
Proactive behavior is an anticipatory behavior to influence both individual and work environment that are beneficial to the organization. It can be affected by various factors, incluidng process control, workloads and intrinsic motivation. This the research is explanatory research. The subject of the research was the Criminal Investigation Unit of Rembang Police Resort. The sampling technique used was census sampling (54 respondents). The data were collected using questionnaire. Then it was analyzed using SEM (Structural Equation Modelling) PLS. Based on the research, it can be concluded that : 1) The process control has a positive and significant effect on proactive behavior, 2) The process control has a negative and significant effect on workloads, 3) The workloads give a positive and significant effect on proactive behavior, 4) The workloads give a negative and significant effect on intrinsic motivation, 5) The intrinsic motivation has a positive and significant effect on proactive behavior, 6) Social capital variable becomes a moderating variable the effect of intrinsic motivation on proactive behaviorKeywords: Control Process, Workloads, Inrinsic Motivation, Proactive Behavior, Sosial Capital